AGREE-S: AGREE II extension for surgical interventions – United European Gastroenterology and European Association for Endoscopic Surgery methodological guide - Logullo, P; Florez, ID; Antoniou, GA; Markar, S; López‐Cano, M; Silecchia, G; Tsokani, S; Mavridis, D; Brouwers, M; Antoniou, SA; Sami Abdel Dayem Amer, Y; Bertolaccini, L; et al. (Wiley, 2022)
Background The Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument has been developed to inform the methodology, reporting and appraisal of clinical practice guidelines. Evidence suggests that the quality of surgical guidelines can be improved, and the structure and content of AGREE II can be modified to help enhance the quality of guidelines of surgical interventions.